News on the Websites of Iraqi Universities - Husni Refat Husni Alashaab; Sofia Mohammed Salim (Genius Journals, 2024)
The research analyses the news published on a sample of Iraqi universities websites, aiming to classify them and identify their subjects, sources, and templates used in its editing process during the period from April 1, 2023, to May 31, 2023. The research is descriptive, and the researchers followed the survey method procedures to achieve the intended objectives. The researchers reached a set of conclusions, which include: the interest of Iraqi universities websites in events related to postgraduate students is significant, and the (Prominence) and (Currency) values are clearly evident in the news. In addition, the inverted pyramid template is used as a fundamental template in the editing process of the news published on the websites.
Keywords: News; Websites; Iraqi; Journalism